CRIMINAL SENTENCING POLICIES FOR INDIVIDUALS WITH DISABILITIES IN CRIMINAL LAW - Lutfah R.; Sugiri B.; Aprilanda N.; Endrawati L. (Russian Journal of Agricultural and Socio-Economic Sciences)
The aim of this research is to examine the Criminal Sentencing Policies for Individuals with Disabilities in Criminal Law. This research employs a normative legal research methodology with an approach based on legislation, comparative analysis, and conceptual analysis. The findings of this research indicate that criminal sentencing policies for individuals with disabilities typically involve adjustments such as special monitoring, reduced penalties, or the use of alternative care systems. These adjustments aim to address their specific needs, avoid inappropriate punishment, and ensure fair treatment within the legal process. The main objective is to ensure justice without disregarding the needs and rights of individuals with disabilities.